The rubber tree RALF peptide hormone and its receptor protein kinase FER implicates in rubber production. (January 2023) - Sui, Jinlei; Xiao, Xiaohu; Yang, Jianghua; Fan, Yujie; Zhu, Sirui; Zhu, Jinheng; Zhou, Binhui; Yu, Feng; Tang, Chaorong
Abstract: RAPID ALKALINIZATION FACTORs (RALFs), which are secreted peptides serving as extracellular signals transduced to the inside of the cell, interact with the receptor-like kinase FERONIA (FER) and participates in various biological pathways. Here, we identified 23 RALF and 2 FER genes in Hevea brasiliensis (para rubber tree), and characterized their expression patterns in different tissues, across the process of leaf development, and in response to the rubber yield-stimulating treatments of tapping and ethylene. Four Hevea latex (the cytoplasm of rubber-producing laticifers)-abundant RALF isoforms, HbRALF19, HbRALF3, HbRALF22, and HbRALF16 were listed with descending expression levels. Of the four HbRALFs, expressions of HbRALF3 were markedly regulated in an opposite way by the treatments of tapping (depression) and ethylene (stimulation). All of the four latex-abundant RALFs specifically interacted with the extracellular domain of HbFER1. Transgenic Arabidopsis plants overexpressing these HbRALFs displayed phenotypes similar to those reported for AtRALFs, such as shorter roots, smaller plant architecture, and delayed flowering. The application of HbRALF3 and HbRALF19 recombinant proteins significantly reduced the pH of Hevea latex, an important factor regulating latex metabolism. An in vitro rubber biosynthesis assay in a mixture of latex cytosol (C-serum) revealed a positive role of HbFER1 in rubber biosynthesis. Taken together, these data provide evidence for the participation of the HbRALF-FER module in rubber production. Highlights: Four latex-abundant RALFs specifically interacted with the extracellular domain of HbFER1. Bioactivity assays reveal functional conservation of latex-abundant HbRALFs. The HbRALF-FER pathway implicates in regulation of pH homeostatis in Hevea latex. Immunoinhibition of HbFER1 affects rubber biosynthesis.